Comparison of hand fluid force and hand kinematics by stroke phase in sprint front crawl swimming between performance level - Koga, D.; Hyodo, H.; Homoto, K.; Tsunokawa, T.; Sengoku, Y.; Kudo, S.; Takagi, H. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION Several methods have been proposed for dividing the front crawl stroke into phases. One of the most popular methods is to divide the stroke into three phases: glide, pull, and push (Chollet et al. 2000). The glide phase starts after the hand enters the water until the hand begins to move backward, the pull phase starts after the glide phase until the hand reaches just below the shoulder, and the push phase starts after the pull phase until the hand exits the water. In front crawl, the first moment of propulsive force, called the "catch", is considered important. The catch is considered to be the beginning of the pull phase, approximately one-third of the way through the underwater stroke (Maglischo, 1993; Chollet et al., 2000). Therefore, it is important to make the better catch motion in the first half of the stroke to obtain greater propulsive force in the subsequent phases. However, the characteristics of the glide phase in fast swimmers are not clear. In addition, it has been reported that the pull and push phases are important in shortdistance front crawl. It has been reported that the lateral velocity of the hand in the push phase is important for achieving high hand propulsive force (Kudo et al. 2023). The angle of attack of the hand is reported to be a factor that influences hand propulsive force and hand surface pressure (Koga et al. 2020). Therefore, it is possible that fast swimmers have distinctive hand velocity and angles of attack during the glide phase and subsequent phases. The purpose of this study was to compare hand fluid forces and hand kinematics during each stroke phase between high-level sprinters and skilled swimmers.